The Proposed Re-introduction of Policing and Crime into the Regulation of Brothels in New South Wales. Issue 2 (1st November 2016) - Crofts, Penny; Prior, Jason
Abstract: Since 1995, brothels in New South Wales have been permitted to operate as legitimate businesses regulated by local councils using planning powers. Despite more than 20 years since decriminalisation and widespread support, there remains an urge by some to heavily regulate the sex industry, reflected in the recently submitted report to the NSW Government from the Select Committee on the Regulation of Brothels (2015). Although the Report supports maintaining decriminalisation, it is dominated by concern about the association of brothels with crime and the consequent need for increased policing. This article argues first that there is little to no evidence to support the criminogenic concerns articulated in the Report. Second, even if these concerns existed, there is nothing to suggest that the proposed measures would provide a solution. Moreover, these proposed reforms reflect a worrying trend in criminal law reform of the expansion of police powers modelled on anti-terrorist legislation, despite existing police powers and criminal offences that are not prosecuted.